PELATIHAN KETERAMPILAN PERDAMAIAN DAN RESOLUSI KONFLIK UNTUK SISWA SEKOLAH MENENGAH PERTAMA (SMP) SEKOLAH LENTERA HARAPAN CURUG, KABUPATEN TANGERANG - Firman Daud Lenjau Lung; Pincanny Georgiana Poluan; Qanszelir G. B. Pandjaitan XIV; Jhon Maxwell Yosua Pattinussa (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2022)
Sustainable peace is the main goal of a country with great diversity like Indonesia. There are concrete efforts that can be made to achieve peace through the educational process, particularly by reaching and training groups in society to have peace knowledge and skills. The strategic target that needs to be outreached is the youth group, considering that this age group serves as the nation's next generation in the future. Junior High School (SMP) students at the Lentera Harapan School (SLH) Curug are considered to need peace skills education because this school is located in a densely populated area and is surrounded by a diverse community. In addition, SLH Curug is located in Curug District, Tangerang, Banten which is a buffer area for the national capital. SLH Curug students are vulnerable to potential conflicts that come from Jakarta. Community service activities were carried out in the form of participatory training that involved all students in interactive activities. There were nine modules being taught to the students. The activity used a constructivist approach through various methods, namely: storytelling, role-playing, brainstorming, group dynamics, discussion, dramatization, group work, case studies, and visualization. Based on the results of the pre-test, post-test, facilitator evaluation, and participant evaluation, the activity went well. Students also gained knowledge and skills about conflict and peace.